Which Symptoms, Complaints and Complications of the Gastrointestinal Tract Occur in Patients With Eating Disorders? A Systematic Review and Quantitative Analysis - Riedlinger, Caroline; Schmidt, Greta; Weiland, Alisa; Stengel, Andreas; Giel, Katrin Elisabeth; Zipfel, Stephan; Enck, Paul; Mack, Isabelle (Frontiers in Psychiatry, 2020)
Background: Eating disorders (ED) such as anorexia nervosa (AN), bulimia nervosa (BN), and binge eating disorder (BED) are often accompanied by a variety of psychological and physical comorbidities. Gastrointestinal (GI) symptoms are a classical feature in most patients with ED. The study heterogeneity regarding this topic is high which makes it difficult to have a clear overview. Therefore, the aim of this systematic review was to provide an overview of subjectively and objectively measured differences and changes in the GI tract in patients with EDs along with the occurance of GI complications. Methods: A systematic literature search was conducted in PubMed, Web of Science and Google Scholar to find all relevant studies examining GI problems in AN, BN, and BED. Quantitative analyses were performed for objective GI physiology measures where applicable. Results: The review differentiated between ED types and also between studies that report GI outcomes of ED in (i) human studies with ED diagnosis excluding case reports giving an overview of GI problems in ED and (ii) case reports with ED diagnosis describing rare GI complications in ED. GI symptoms and impaired gastric transit were frequent features of EDs with specific differences found for the ED types. During the time course of treatment, GI symptoms changed and/or improved but not completely. GI complications extended the range of GI problems observed by including a variety of serious complications such as gastric dilatation. Conclusions: Problems of the GI tract are frequent in patients with ED and it is not unlikely that they complicate therapy, especially in patients with AN. Registration: This review is registered at PROSPERO with the ID: CRD42019100585